Pembatalan Putusan Arbitrase Nasional Oleh Pengadilan Negeri - Muhammad Andriansyah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: The National Arbitration Award Cancellation By Court. Article 70 of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, stating that the award can only be canceled if it is thought to contain elements of letter/false documents, or documents found hidden by the other party, or a decision that is taken from the results of deceit trick performed by one of the parties in the dispute. To prove whether or not one of the above three elements must be proved by a court decision. If the District Court stated that the reasons are evident, then the arbitration award may be canceled, if not proven, the Court should reject the application for cancellation of the arbitration decision. But in practice, there is still the District Court received the request for cancellation of arbitration outside the context of Article 70 of Law No. 30 of 1999 as stated in the South Jakarta District Court. Abstrak: Pembatalan Putusan Arbitrase Nasional Oleh Pengadilan Negeri. Pasal 70 Undang-Undang Nomor 30 Tahun 1999 Tentang Arbitrase dan Alternatif Penyelesaian Sengketa, menyatakan bahwa putusan arbitrase hanya dapat dibatalkan jika diduga mengandung unsur-unsur surat/dokumen palsu, atau ditemukan dokumen yang disembunyikan oleh pihak lawan, atau putusan yang diambil dari hasil tipu muslihat yang dilakukan oleh salah satu pihak dalam pemeriksaan sengketa. Untuk membuktikan ada atau tidaknya salah satu dari tiga unsur diatas harus dibuktikan dengan putusan pengadilan. Apabila Pengadilan Negeri menyatakan bahwa alasan-alasan tersebut terbukti, maka putusan arbitrase dapat dibatalkan, apabila tidak terbukti, maka Pengadilan Negeri harus menolak permohonan pembatalan putusan arbitrase. Akan tetapi dalam pelaksanaannya, Pengadilan Negeri masih ada yang menerima permohonan pembatalan arbitrase di luar konteks pasal 70 Undang-Undang No 30 Tahun 1999 sebagaimana tertuang dalam putusan Pengadilan Negeri Jakarta Selatan. DOI: 10.15408/jch.v1i2.1472